HUKUM DAN PEDOMAN ZAKAT FITRAH DENGAN UANG (KAJIAN FATWA MUI PROVINSI DKI JAKARTA, NO. 1 TAHUN 2018) - Fuad Thohari; Mohammad Syairozi Dimyathi Ilyas (Universitas Islam Negeri Mataram, 2020)
The Trend of Muslims lately-probably due to consideration of the use of money more practical and easy- make the payment of Zakat Fitrah conventional in form rice (the staple food of the majority of Muslims in Indonesia that following syafi’i mazhab) began to shift and replaced with the money following the Hanafi mazhab. The tendencies of Muslims in Indonesia that convert zakat Fitrah from rice become money as Hanafi mazhab, must be tested in terms of the taqlid procedures to avoid deviations and talfiq prohibited. In Ramadan year 1441 H when the Covid-19 pandemic occurs, the government prohibits the mass crowd and requires physical distancing, the payment of zakat Fitrah with money transfer becomes one of the best solutions to avoid physical contact that potentially transmit the virus.This paper, specifically reviewing zakat Fitrah with money, starting from: the understanding of zakat Fitrah, the procedure of Zakat Fitrah with money according to the Hanafi Mazhab, and other issues related. This study is not only beneficial for academics and Muslims who pay Zakat Fitrah with money, but also beneficial to the Committee of Zakat Collector, Baznas, Laznas, and other institutions as a guideline for zakat Fitrah with money. This issue is examined by the library research referring to the literature that contains ulama fatwas